Doing Mission Dalam Pendidikan Agama Kristen (PAK) Menyambut Era Society 5.0 - Febriaman Lalaziduhu Harefa; Jeane Paath (Sekolah Tinggi Theologia Ebenhaezer Tanjung Enim, 2022)
Society 5.0 has a positive impact on human life, as well as a negative impact. Especially in the field of education, it has a significant impact, especially if it is related to the ministry of the mission of the Kingdom of God. This paper tries to describe the essence of the mission in Christian Religious Education in the era of Society 5.0 and the appropriate learning methods to be practiced by Christian teachers. The approach taken is qualitative with library research. The result builds the foundation of the Biblical mission and the constructive-contextual philosophy of Christian Religious Education. The method in learning is to build a technology-based, character-based learning approach and efforts to integrate mission experience, Christian mission theory and artificial intelligence